Hardness and Wear Analysis of Brake Pads Made from Sugarcane Bagasse and Iron Powder as Epoxy Matrix Reinforcement - Prasetyo , Joko Hari; Bahri , Mokh. Hairul; Putra Nusantara , Ardhi Fathoni Syam (Universitas Muhammadiyah Jember, 2023)
Brake lining is a component that has the function of slowing or stopping the speed of a vehicle. Brake linings sold on the market are generally made from asbestos which is not friendly to health and the environment. Therefore, there is a need for alternative ways of making brake linings with materials that are safe for health and the environment, one of which is by using sugarcane bagasse waste, seeing that the nature of sugarcane bagasse is fibrous so it has the potential to be used as an alternative material for brake lining mixtures. The aim of this research is to analyze the best hardness and wear of composite brake pads made of bagasse material and iron powder as reinforcement with an epoxy matrix through the Shore D hardness test and Oghosi wear test, with the composition of bagasse ranging from 35%, 40%, 45% varying with iron powder of 15%, 10%, 5% and mixed with 50% epoxy resin with the same content. Shore D hardness test results obtained the highest hardness, namely at a volume fraction of 35%: 15%: 50% with a value of 72.5 HD. In the Oghosi wear test results, the lowest wear was in the volume fraction of 35% : 15% : 50% with a wear value of 0.000203 Ws;mm 3 /kg.m. The results of this research show that the large percentage of bagasse and iron powder mixed will affect the hardness and wear values of the brake pads.